Canine Events As A Segment Of Tourism Offer - Matejević, Milosava (Turizam, 2017)
A well-planned and organized dog competition is a serious event with a large number of visitors. It has great cynologic, but also economic and tourist importance for the city and the country in which it is organized. Seriously organized dog competitions with a large number of registered dogs and competitors, regardless of whether they are of national or international significance, bring together a large number of people, among them not only competitors, but also members of the organizing team, judges, trainees, volunteers, exhibitors, veterinarians, observers and others. Among the visitors, there are a large number of people traveling far from the place of residence to participate in these competitions. Canine events (competitions in the work and beauty of dogs) are characterized as specific, thematic, interactive and public events with sports-recreational, business and entertainment character. During these events dogs are classified in beauty or a certain type of work. As such, dog events can significantly contribute to the improvement of the tourism product of a certain area, as well as the entire touristic product of Serbia.